Classification of knowledge in the discourses of al-Shafi'i (d.204/820) and al-Ghazali (d.505/1111) : a comparative study - Nurul Hidayah binti Aziz (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
This study attempts to explore and analyse al-Shafi'i's (d. 204/820) and al-Ghazali's (d. 505/1111) classifications of knowledge. It also aims to analyse the influences of those scholars' thoughts in the modern frame i.e. al-Attas's classifications of knowledge. Besides the differences between al-Shafi'i's and al-Ghazali's classifications of knowledge, this study tries to find the meeting points between those tripartite scholars on classifications of knowledge in Islamic epistemology. From the collection of data of primary sources, this study then carries out data analysis by studying those tripartite thoughts. Data are presented to differentiate those scholars' understanding of classifications of knowledge. The findings indicate that al-Shafi'i has influence al-Ghazali on Individual Obligations (Fard al-'Ayn) and Collective Obligations (Fard al-Kifayah). In addition, al-Ghazali develops the scope of classifications of the former with the concept of soul and expands the latter to non-religious sciences. Meanwhile, al-Attas subsequently obliged upon individuals the study of al-Qur'an and al-hadith, where there is a variety between al-Shafi'i's and al-Ghazali's understandings of Individual Obligations (Fard al-'Ayn). Nevertheless, al-Attas is influenced by al-Shafi'i, though predominantly al-Ghazali. The findings also demonstrate that there are some development and enhancement with various understandings from the similarities of classifications of knowledge. This study is noteworthy in order to perceive the development and amelioration on classifications of knowledge, beginning with al-Shafi'i until they reflect modern occurrence.